2017
DOI: 10.1002/2017jb013965
|View full text |Cite
|
Sign up to set email alerts
|

A fluid‐rich layer along the Nankai trough megathrust fault off the Kii Peninsula inferred from receiver function inversion

Abstract: Investigation of fluid distribution along megathrust faults is an important issue, since the fluid affects frictional properties and thus slip behavior on faults. Scattered teleseismic phases, or receiver functions (RFs), have made significant contributions to understanding the fluid content of subducting plates beneath the onshore regions but have been rarely applied in offshore settings. In this study, we conducted receiver function inversion analysis to investigate detailed seismic properties near the megat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…This is due to intense water reverberations dominating the vertical component records. Recent efforts have overcome this difficulty and allowed for investigating subsurface structure using high-frequency receiver functions with data from offshore observatories (Akuhara et al, 2016(Akuhara et al, , 2017(Akuhara et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to intense water reverberations dominating the vertical component records. Recent efforts have overcome this difficulty and allowed for investigating subsurface structure using high-frequency receiver functions with data from offshore observatories (Akuhara et al, 2016(Akuhara et al, , 2017(Akuhara et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Recently several methods have been developed to account for these problems including transfer function modelling (Audet, 2016), inverse water-layer filter (Akuhara and Mochizuki, 2015;Akuhara et al, 2016) and transdimensional inversion (Akuhara et al, 2019). Akuhara et al (2017) applied inverse water-layer filter to OBS stations located in the Nankai trough and found the presence of a thin low-velocity zone (LVZ) of a thickness of 0.2-1.2 km with a S wave velocity of 0.7-2.4 km/s along the plate interface at 15-20 km depth. Using the transdimensional inversion method, Akuhara et al (2020) also found a LVZ ∼1 km thick at the plate interface at ∼6 km depth in the shallow part of Nankai trough forearc.…”
Section: Receiver Functionsmentioning
confidence: 99%
“…In principle, the receiver function technique should provide the best resolution on the age‐dependence, depth, and sharpness of a sharp velocity gradient, making it a promising seismic technique for investigating the lithosphere structure of an oceanic plate (Akuhara et al., 2016, 2017; Akuhara & Mochizuki, 2015; Audet, 2016; Hannemann et al., 2017; Janiszewski & Abers, 2015; Kawakatsu et al., 2009; Kumar et al., 2011; Liu et al., 2020; Olugboji, Park, Karato, & Shinohara, 2016; C. A. Rychert et al., 2013, 2018a). However, it has been pointed out that in the seafloor environment they can be complicated by sediment reverberations and should be treated with caution (Audet, 2016; Kawakatsu & Abe, 2016; Olugboji, Park, & Karato, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the receiver function technique should provide the best resolution on the age-dependence, depth, and sharpness of a sharp velocity gradient, making it a promising seismic technique for investigating the lithosphere structure of an oceanic plate (Akuhara et al, 2016(Akuhara et al, , 2017Akuhara & Mochizuki, 2015;Audet, 2016;Hannemann et al, 2017;Janiszewski & Abers, 2015;Kawakatsu et al, 2009;Kumar et al, 2011;Liu et al, 2020;Olugboji, Park, Karato, & Shinohara, 2016;C. A. Rychert et al, 2013C.…”
mentioning
confidence: 99%